Towards green membranes: Repurposing waste polypropylene with a single plant-based solvent via tandem spin-casting and annealing - Saleem, Junaid (2024)
A key aspect of advancing sustainable membrane technology is to source eco-friendly polymers, such as recycled plastic waste, use renewable plant-based solvents, and limit the number of solvents used in dissolution-precipitation processes. In this study, we upcycle polypropylene PP waste into bi-layered microporous superhydrophobic membranes using a single plant-based solvent, Cymene, through tandem spin-casting and annealing. The surface roughness and hydrophobicity of the top layer enhance selectivity, while the presence of micropores ensures efficient liquid passage and high permeability. The microporous bottom layer serves as a substrate for the top layer, providing structural support. Various annealing conditions were employed to optimize hydrophobicity, roughness, porosity and strength of as-prepared membranes, yielding high permeance and outstanding separation efficiency. The fabricated membranes were subjected to oil–water emulsion separations, demonstrating a contact angle exceeding 155° and a surface roughness of 123 nm, resulting in an organic solvent flux of 14,000 Lm-2h−1 with a 96 % water rejection. Tensile strength and strain % were found to be 13–28 MPa and 20–27 %, respectively. This research provided access to environmentally friendly membranes, adding value to plastic waste with potential benefits to both the polymer and membrane industries as they transition towards a circular economy.